Effect of hydrate distribution on effective thermal conductivity changes during hydrate formation in hydrate-bearing quartz sands - He, Juan; Li, Xiaosen; Chen, Zhaoyang; You, Changyu; Yan, Kefeng; Xia, Zhiming; Li, Qingping (International Journal of Heat and Mass Transfer, 2021)
The effect of hydrate distribution on the effective thermal conductivity changes of the actual hydrate-bearing sediments is uncertain. To define this effect, in the hydrate-bearing quartz sands, the effective thermal conductivity was measured by the transient hot-wire method, and hydrate distribution was analyzed by the electrical resistance changes. At first, the effective thermal conductivity changes were investigated from gas saturation, gas pressure, water saturation, water pressure, and temperature. Afterward, in three kinds of hydrate formation processes, compared with hydrate distribution, the changing trends of the effective thermal conductivity at five measuring points were analyzed. The results showed that the effective thermal conductivity was increased with decreasing gas saturation and increasing water saturation or water pressure, and impacted slightly by gas pressure and temperature. Moreover, at five measuring points, the non-uniform hydrate distribution caused different changing trends of the effective thermal conductivity during hydrate formation. In the excess-water setting, an increasing trend was only observed at some local measuring point. The decreasing trends at the most of the measuring points were governed by the reduced water distribution. But in the excess-gas setting, at the most of the measuring points, this increasing trend was observed and controlled by the enlarged hydrate distribution. Besides, for some actual sediments in the excess-water setting, hydrate distribution may be not the key factor of the effective thermal conductivity changes, and further studies were required. This research could offer some valuable reference to the thermal properties in the actual sediments. (C) 2021 Elsevier Ltd. All rights reserved.